Influence of microwave drying on quality parameters of foamed Nagpur Mandarin (Citrus reticulata) juice - Bhagyashree Nivrutti Patil; Suchita V. Gupta; Nivrutti.B. Patil; Nileshwari Yewle (Heliyon, 2024)
In the world of industrial drying processes, foam mat microwave drying is a significant and valuable approach. Its advantages include increased drying effectiveness, preservation of product quality, energy and cost savings, flexibility in application, and improved safety. Development of Nagpur mandarin juice powder is tedious and time-consuming due to its bitter test and less total soluble solid, therefore the present research carried out with the process parameters for microwave drying include microwave power levels (180, 360, 540, 720, and 900 W) and drying bed thicknesses (2, 4, and 6 mm). Foamed juice is produced using soy protein isolate (2.10 %), GMS (2.75 %), CMC (1.75 %), and sugar (5.10 %), with whipping times of 8 min. Additional foaming agents include guar gum (0.45 %), soy protein isolate (3.30 %), and sugar (10 %) with whipping times of 6 min. The optimal conditions for drying Nagpur mandarin juice were determined through analysis using Design-Expert 11.0.4.1 software. These conditions include 540 W of microwave power, a drying bed thickness of 3 mm, and the use of a foaming agent comprising 2.10 % soy protein isolate, 2.75 % GMS, 1.75 % CMC, and 5.10 % sugar, with an 8-min whipping period. Under these optimized conditions, the resulting powder exhibited the following characteristics: color b value of 19.59, ΔE (change in color) of 6.24, acidity of 0.40 %, ascorbic acid content of 36.64 mg/100 g, water activity of 0.26, drying time (in minutes), and overall acceptability rating of 7.77. These findings highlight the effectiveness of the optimized process parameters in achieving desirable quality attributes for Nagpur mandarin juice powder production.